General Characteristics of the Judicial System of Ukraine – Cossack Hetmanate (1722-1760) - Glamazda, P.; Гламазда, П. (Східноєвропейський національний університет імені Лесі Українки, 2017)
The article contains the research of general characteristics of the judicial system, which existed in Ukraine in 1722-1760, that is based on historical and legal analysis of sources of law of Ukraine – Cossack Hetmanate, monographs and scientific works. The role, location and competence of the authorities that carried out justice in this period were defined in the article. It was established that the efforts ofthe hetmans and Cossack officers in reforming of the judicial system were aimed at correcting deficiencies, such as: litigation in courts beyond their competence, low qualification of judges in village courts, disregardof the principle of collective proceedings etc. It was justified that while preserving the pace of the development and autonomy of Ukraine – Cossack Hetmanate in general,its judicial system could have formed the basis for the creation of a strong and effective European judicial system. В статті на підставі історико-правового аналізу джерел права України-Гетьманщини, монографічної літератури та наукових праць здійснено загальну характеристику судової системи, яка діяла на території України в1722–1760 роках. Визначено роль, місце та компетенцію органів, що здійснювали правосуддя у зазначений історичний період. Встановлено, що зусилля гетьманів та козацької старшини у сфері реформування судової системи були направлені на виправлення недоліків, зокрема, розгляду справ судами поза їхньою компетенцією, низької кваліфікації суддів сільських судів, нехтування принципом колегіальності судового розгляду тощо. Обгрунтовано, що за умов збереження такого темпу розвитку та автономії України-Гетьманщини загалом судова система могла б стати основою для створення потужної та дієвої європейської судової системи.
Загальна характеристика судової системи України-Гетьманщини у1722– 1760 роках.
Keywords: historical and legal analysis; Ukraine – Cossack Hetmanate; judicial system; judicial system reform; Pavlo Polubotok; Danylo Apostol; історико-правовий аналіз; Україна-Гетьманщини; судова система; судоустрій; реформа; Павло Полуботок; Данило Апостол